The light we carry overcoming in uncertain times - Obama, Michelle (London Penguin Books, 2022)
Michelle Obama offers readers a series of fresh stories and insightful reflections on change, challenge, and power, including her belief that when we light up for others, we can illuminate the richness and potential of the world around us, discovering deeper truths and new pathways for progress. Drawing from her experiences as a mother, daughter, spouse, friend, and First Lady, she shares the habits and principles she has developed to successfully adapt to change and overcome various obstacles?the earned wisdom that helps her continue to ?become.? She details her most valuable practices, like ?starting kind,? ?going high,? and assembling a ?kitchen table? of trusted friends and mentors. With trademark humor, candor, and compassion, she also explores issues connected to race, gender, and visibility, encouraging readers to work through fear, find strength in community, and live with boldness.
Keywords: Presidents' spouses